PLASTIK LOW-DENSITY POLYETHYLENE PADA CAMPURAN ASPAL AC-WC - Sesep Fahmi Aminudin; Athaya Zhafirah (Racic : Rab Construction Research, 2023)
The problem of environmental pollution due to the continuous increase in plastic over time is a problem that is being faced worldwide, especially in Indonesia. Plastic is trendy and used in everyday life. One effort to reduce the amount of plastic is to use it as an additive to asphalt mixtures. The plastic in the asphalt mixture is used to coat the aggregate. This study aimed to determine Marshall's characteristics due to adding LDPE (low-density polyethylene) plastic as a substitute for asphalt in the AC-WC mixture. The research was conducted using experimental methods in the laboratory. Various LDPE plastic mixtures used were 0%, 4%, and 6% by weight of asphalt. The results showed that the asphalt mixture added with 4% and 6% LDPE plastic could increase density, flow, VFB, and MQ values. However, for stability values, VIM and VMA asphalt mixtures without LDPE were smaller than asphalt mixtures with 4% and 6% LDPE.